PERLINDUNGAN HUKUM TERHADAP KONSUMEN AKIBAT BEREDARNYA PENJUALAN ELEKTRONIK HANDPHONE JENIS REPLIKA DAN PARALLER IMPORT (BLACKMARKET)DI KOTA PEKANBARU - Ahmad Ade Saputra; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The process of running a business venture in Indonesia, often business people forget how important the rights of consumers to be met under the Consumer Protection Act No. 8 of 1999 (BFL). As the times people are starting to think practically it mebuat society as consumers become more consumptive. Less watchfulness consumers seem to have been used by the electronics businesses by selling mobile phone type of replica and paraller import (Blackmarket) with a quality that does not meet national standards. Based on the understanding of the authors formulated two formulation of the problem: first, any form of violation committed businesses in the sales of mobile electronics and Blackmarket replica in Pekanbaru. Second, how is the responsibility of businesses to consumers who sell mobile electronics and Blackmarket types of replicas in Pekanbaru.This type of research can be classified into types of juridical sociological research, because in this study the authors conducted a study of spaciousness. Location and population studies along with samples in this paper is the mobile electronic shopping mall in Pekanbaru Mall and Plaza Senapelan located in the city of Pekanbaru. The data source consists of primary and secondary data, engineering data collection is by interview along with questionnaires to consumers / buyers as respondents and discussion with entrepreneurs / seller as a practitioner in the field.Obtained results of this study: first, forms of violations committed by businesses in the sales of mobile electronics and Blackmarket replica. Second, the responsibility of the businesses that sell to the consumer electronics and mobile phones type of replicas Blackmarket in Pekanbaru.Obtained results of this study, there are four main problems that can be concluded first, namely, the right of consumers to correct information, clear and honest about the condition and guarantee of the goods and / or services. Secondly, violation of consumers' right to obtain compensation and / or replacement, if the goods and / or services received or not in accordance with the agreement as it should. Thirdly, businesses that commit a prohibited act that offer goods and / or services incorrectly, and / or as if the goods are in good condition and / or new. Fourth, a violation of the exoneration clause prohibited the inclusion in the regulation of BFL. Saran, is expected prudence and knowledge of consumers into buying mobile products need to be improved. In addition, it is expected to supervision and enforcement of government in providing protection to consumers in the city of Pekanbaru needs to be maximized implementation.keywords: protection, electronics, replica, import paraller